Advanced geotechnical engineering soil-structure interaction using computer and material models - Desai, C. S. (Chandrakant S.) 1936-; Zaman, Musharraf (CRC Press, 2004)
This book provides readers with a comprehensive treatment of computer methods so that they can use them for teaching, research, and solution of a wide range of practical problems in geotechnical engineering. It discusses factors such as in-situ conditions, elastic, plastic and creep deformations, stress path, volume change, existence of fluids (water), non-homogeneities, inherent and induced discontinuities leading to softening and failure, healing or strengthening, and type of loading